2017
DOI: 10.1186/s12879-017-2636-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of candidemia in epidemiology and risk factors among cancer patients in a cancer center of China: an 8-year case-control study

Abstract: BackgroundCandidemia is the worldwide life-threaten disease, especially in cancer patients. This study was aimed to identify and evaluate the risk factors of candidemia in cancer patients, which will prompt the improvement on current therapeutic strategies and prognosis.MethodsA retrospective, case-control study was conducted from inpatients of Tianjin Medical University Cancer Institute and Hospital, during 2006 to 2013. Analyses were performed between cancer patients with candidemia as study case, and patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
2
15

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 44 publications
8
42
2
15
Order By: Relevance
“…Overall, paediatric patients who are frequently exposed to high‐risk medications or have severe underlying diseases might be at risk of nosocomial candidaemia. We observed that patients with different types of cancer, that is haematological malignancies and/or non‐haematological malignancies (74.3%) because of their immunocompromised status, were much more susceptible to candidaemia than immunocompetent children, which corresponds with other studies . In fact, 78% of cancer patients received chemotherapy, corticosteroids, broad‐spectrum antibiotic therapy or prophylaxis, which was attributed to the observed high correlation of cancer with candidaemia.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Overall, paediatric patients who are frequently exposed to high‐risk medications or have severe underlying diseases might be at risk of nosocomial candidaemia. We observed that patients with different types of cancer, that is haematological malignancies and/or non‐haematological malignancies (74.3%) because of their immunocompromised status, were much more susceptible to candidaemia than immunocompetent children, which corresponds with other studies . In fact, 78% of cancer patients received chemotherapy, corticosteroids, broad‐spectrum antibiotic therapy or prophylaxis, which was attributed to the observed high correlation of cancer with candidaemia.…”
Section: Discussionsupporting
confidence: 90%
“…The underlying diseases and risk factors for candidaemia in the various age groups of paediatric patients are different . For instance, as shown in the current study, prematurity, CVC use, mechanical ventilation, broad‐spectrum antibiotic therapy or prophylaxis, receipt of TPN, and long stay at the ICU were the major predisposing factors for neonatal candidaemia, whereas cancer, CVC use, chemotherapy, corticosteroid therapy and antifungal and antibiotic therapy or prophylaxis accounted for most of the candidaemia among infants and children.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Disseminated Candidal infections can occur in immunocompromised hosts such as patients receiving chemotherapy for malignancies, and Candida tropicalis may be involved in approximately 8% of cancer cases (Li et al, 2017). Culture of fungal abscess using traditional media may have low yield if the specimen is collected after antifungal therapy.…”
Section: Introductionmentioning
confidence: 99%